Thermochromic properties of some colored oxide materials - Gabriel Ferro; Davy Carole; François Cauwet; Loren Acher; Hyewon Ji; Rodica Chiriac; François Toche; Arnaud Brioude (Optical Materials: X, 2022)
The thermochromic properties up to 500 °C of some colored, commercial and non-toxic oxides were studied. It includes Bi2O3, Fe2O3, In2O3, WO3, Er2O3, YAG:Ce (Ce doped yttrium aluminum garnet Y3Al5O12) and YInMn-Blue (Mn doped yttrium indium oxide YInO3). From the CIELAB colorimetric parameters (L*a*b*), evolution of the color contrast ΔE with temperature was calculated. It allowed estimating that most of these oxides change color reversibly with increasing temperature, the strongest thermochromism being found for Bi2O3 (ΔE ∼ 65 at 500 °C). Two exceptions were identified: i) Er2O3 which stayed almost identically pink with ΔE<7 even at 500 °C and ii) WO3 which original color was not recovered upon cooling back to room temperature. While the color change of the other oxides was gradual with increasing temperature, YAG:Ce compound behaved differently since its thermochromicity abruptly started above 300 °C. DSC analyses did not allow detecting any physico-chemical event in relation with these peculiarities. The obtained datasets for all these compounds can be used for anticipating the thermochromic properties of these powders and the blends made out of them.